2021
DOI: 10.1038/s41598-021-81014-z
|View full text |Cite|
|
Sign up to set email alerts
|

ExoFiT trial at the Atacama Desert (Chile): Raman detection of biomarkers by representative prototypes of the ExoMars/Raman Laser Spectrometer

Abstract: In this work, the analytical research performed by the Raman Laser Spectrometer (RLS) team during the ExoFiT trial is presented. During this test, an emulator of the Rosalind Franklin rover was remotely operated at the Atacama Desert in a Mars-like sequence of scientific operations that ended with the collection and the analysis of two drilled cores. The in-situ Raman characterization of the samples was performed through a portable technology demonstrator of RLS (RAD1 system). The results were later complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…This means that highly resistant lipid compounds and hyperarid evaporitic paleolakes/basins combine to increase the chances of uncovering more intact hydrocarbon skeletons with perhaps still intact ether backbones or isoprenoidal chains. Further, accessing UV-, perchlorate-, and chlorate-devoid samples (martian iron [hydr]oxide-rich conditions also favor the accumulation of chlorates) (Qu et al , 2022 ) using enhanced drills such as the 2 m device loaded onto the Rosalind Franklin rover (Veneranda et al , 2021 ) could be deemed as an attainable objective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that highly resistant lipid compounds and hyperarid evaporitic paleolakes/basins combine to increase the chances of uncovering more intact hydrocarbon skeletons with perhaps still intact ether backbones or isoprenoidal chains. Further, accessing UV-, perchlorate-, and chlorate-devoid samples (martian iron [hydr]oxide-rich conditions also favor the accumulation of chlorates) (Qu et al , 2022 ) using enhanced drills such as the 2 m device loaded onto the Rosalind Franklin rover (Veneranda et al , 2021 ) could be deemed as an attainable objective.…”
Section: Discussionmentioning
confidence: 99%
“…Layered outcrops in the Atacama have been scrutinized with laser Raman spectroscopy to inspect the analogous scenario that the ChemCam instrument from Curiosity would encounter by Aeolis Mons, the central peak within Gale Crater (Sobron et al , 2013 ). Similarly, an emulator of the Raman Laser Spectrometer onboard the ExoMars Rosalind Franklin rover (Lopez Reyes et al , 2019 ) was tested in the quartz- and phyllosilicate-rich region of Antofagasta (Veneranda et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This instrument represents the key analytical tool for the RLS science team to investigate the potential scientific capability of the flight model soon operating on Mars. As such, recent research confirmed the capability of the RLS ExoMars Simulator to (1) detect biomarkers in extreme environments [68], (2) identify shock‐related metamorphism of impacted minerals [69], (3) extrapolate the elemental composition of mineral phases within solid solution series [70], and (4) extrapolate semiquantitative values through the chemometric analysis of ExoMars‐like Raman datasets (39 spectra per sample) [71, 72].…”
Section: Raman Instrumentsmentioning
confidence: 97%
“…[12] 2-Understanding of the analytical capabilities of RLS in the ExoMars rover to help define the operational interface with the carrousel and rover: the scientific analysis of powdered samples in a multipoint fashion returned relevant data and information to the definition of the onboard operation mode. [18][19][20][21][22][23][24][25][26] 3-Preparation for the mission: Investigations on Martian analog samples relevant to the mission's landing site (Oxia Planum) can be carried out with this system both in laboratory and field conditions. These tests are performed jointly with select analysis on the RLS Flight Spare (FS) model, to evaluate the detection capabilities by the instrument with the expected sample types.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of the analytical capabilities of RLS in the ExoMars rover to help define the operational interface with the carrousel and rover: the scientific analysis of powdered samples in a multipoint fashion returned relevant data and information to the definition of the onboard operation mode. [ 18–26 ]…”
Section: Introductionmentioning
confidence: 99%